2015
DOI: 10.1002/lary.25721
|View full text |Cite
|
Sign up to set email alerts
|

Can perioperative acupuncture reduce the pain and vomiting experienced after tonsillectomy? A meta‐analysis

Abstract: NA. Laryngoscope, 126:608-615, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 34 publications
1
24
0
1
Order By: Relevance
“…Ondansetron is a serotoniergic antagonist and is generally tolerated quite well in children. But, it is expensive and has serious adverse effects including headache, fever, dizziness, abdominal cramps, transient elevation in plasma aminotransferase and bilirubin levels, and anaphylactic or anaphylactoid reactions . It is believed that serotoniergic antagonists are partially effective as most of them block only one type of receptor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ondansetron is a serotoniergic antagonist and is generally tolerated quite well in children. But, it is expensive and has serious adverse effects including headache, fever, dizziness, abdominal cramps, transient elevation in plasma aminotransferase and bilirubin levels, and anaphylactic or anaphylactoid reactions . It is believed that serotoniergic antagonists are partially effective as most of them block only one type of receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Many treatment modalities have been used as an effective means to control postoperative morbidities in children after tonsillectomy. However, there is no agreement on any particular medication, technique, or tool .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of other articles have also shown some perceived pain relief without significant adverse effects due to acupuncture. [136,137]…”
Section: The Mind–body Approach To Painmentioning
confidence: 99%
“…Acupuncture may also activate endogenous pain inhibitory pathways [9]. Clinical studies have shown that acupuncture is a useful adjuvant treatment in post-operative pain [9], including post-tonsillectomy pain [7,8]. However in a home situation, the large majority of patients would be reluctant to needle themselves or their families.…”
Section: Acupuncturementioning
confidence: 99%